1999
DOI: 10.1021/ja9900757
|View full text |Cite
|
Sign up to set email alerts
|

Titanocene Borane σ-Complexes

Abstract: The chemistry of titanocene bisborane complexes Cp2Ti(HBcat‘)2 (1a − g) (HBcat‘ = catecholborane or a substitued catecholborane) and monoborane complexes Cp2Ti(HBcat‘)(L) (2 − 4) (L = PMe3, PhSiH3, or PhCCPh) is reported. These complexes are unusual σ-complexes. The B−H bond in the catecholborane of 1 acts as a two-electron-donor ligand. The 4-tert-butyl version 1a was studied in depth and underwent ligand substitution reactions with PMe3, CO, PhSiH3, and PhCCPh. The products of the reaction of 1a with PMe3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 67 publications
4
87
1
3
Order By: Relevance
“…[14] They also found that the reaction of [Ti(Cp) 2 (PMe 3 ) 2 ] with PhSiH 3 gives a close analogue of 1, namely, the silane s complex [Ti(Cp) 2 (PMe 3 )(h 2 -H 3 SiPh)]. [15] A complex reported by Hartwig et al [16] as [Ti(Cp) 2 (h 2 -HBcat')(h 2 -H 3 SiPh)] (cat' = catechol) was later suggested to be a silylborato complex [Ti(Cp) 2 (h 2 -H 2 Bcat')(SiH 2 Ph)] on the basis of theoretical studies. [17] No fully authenticated, classical mononuclear silyl hydride complex of Ti IV has been reported to date.…”
Section: Introductionmentioning
confidence: 89%
“…[14] They also found that the reaction of [Ti(Cp) 2 (PMe 3 ) 2 ] with PhSiH 3 gives a close analogue of 1, namely, the silane s complex [Ti(Cp) 2 (PMe 3 )(h 2 -H 3 SiPh)]. [15] A complex reported by Hartwig et al [16] as [Ti(Cp) 2 (h 2 -HBcat')(h 2 -H 3 SiPh)] (cat' = catechol) was later suggested to be a silylborato complex [Ti(Cp) 2 (h 2 -H 2 Bcat')(SiH 2 Ph)] on the basis of theoretical studies. [17] No fully authenticated, classical mononuclear silyl hydride complex of Ti IV has been reported to date.…”
Section: Introductionmentioning
confidence: 89%
“…Hartwig 2 ] in 1996 on the basis of NMR spectroscopy, X-ray diffraction, and MP2 calculations. [52,53] There are indeed no examples of structures incorporating a M(h 2 -C-H) 2 fragment, but it is interesting to mention some related agostic structures. The cationic iridium complex [Ir(H) 2 (PtBu 2 Ph) 2 ]…”
Section: Structures With Two S Ligandsmentioning
confidence: 99%
“…[23] More recently, reactions involving Me 3 P ¥ BH 3 and Me 3 P ¥ BH 2 BH 2 ¥ PMe 3 have resulted in BÀH bond activation and led to structurally characterized examples of mononuclear and dinuclear metal boryl complexes. [24] In addition, sborane [25] complexes and h 1 -borane [26] complexes have also been reported.…”
Section: Introductionmentioning
confidence: 99%